2016
DOI: 10.5430/jha.v5n3p67
|View full text |Cite
|
Sign up to set email alerts
|

Motivating health professionals through control mechanisms: A review of empirical evidence

Abstract: This paper summarizes the findings of the literature on the levers used in the health care sector to motivate workers, with a particular focus on the impact of management control tools (such as Performance Measurement Systems (PMS) and Pay for Performance) on motivation. A review of the literature was carried out using the ISI Web of Knowledge, Pubmed and JSTOR search engines on the topic of motivation of health care workers, including, if possible, all the involved categories of employees. The research focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Obviously, the healthcare systems, in which medical staff is properly motivated, show a higher level of effectiveness and efficiency and, vice versa, improperly motivated a lower level [3,21,61,64,70,73]. Recent research on healthcare performance in Europe applied data envelopment analysis and revealed countries with high and low effectiveness and efficiency rates continent-wide [46].…”
Section: Study Of Health Professionals' Motivation and Efficiency Of ...mentioning
confidence: 99%
“…Obviously, the healthcare systems, in which medical staff is properly motivated, show a higher level of effectiveness and efficiency and, vice versa, improperly motivated a lower level [3,21,61,64,70,73]. Recent research on healthcare performance in Europe applied data envelopment analysis and revealed countries with high and low effectiveness and efficiency rates continent-wide [46].…”
Section: Study Of Health Professionals' Motivation and Efficiency Of ...mentioning
confidence: 99%
“…[1][2][3][4][5][6] Recent research on healthcare performance in Europe applied data envelopment analysis and revealed countries with high and low effectiveness and efficiency rates continent-wide. 7 Generally speaking, healthcare effectiveness is measured as the ratio of healthy years lived and life expectancy per infant mortality [4][5][6] ; however; utilising Lo Storto and Goncharuk's 7 approach effectiveness of a healthcare system is based solely on quality of care. Furthermore, healthcare efficiency reflects how many medical doctors, nurses and other health professionals in correlation with available beds in hospitals are needed to meet the demand for healthcare services among the population of a country.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that healthcare systems in which medical staff are properly motivated show a higher level of effectiveness and efficiency and, vice versa, improperly motivated a lower level 1‐6 . Recent research on healthcare performance in Europe applied data envelopment analysis and revealed countries with high and low effectiveness and efficiency rates continent‐wide 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The research is inspired by the need of healthcare entities to rationalize the resources available (Leotta and Ruggeri, 2012), giving health professionals awareness of the costs related to alternative choices of intervention and treatment of the same pathology (Russo, 2011;Nuti et al, 2010), engaging them to optimize the choices and to improve the organizational and operational processes that lead to the expected outcomes (Smaldone and Vainieri, 2016). Many previous studies have already analyzed in depth the cost accounting systems in alternative care pathways, through the use of activity based and micro-costing approaches (Chan & Ching, 1993;Evans et al, 1997;Ross, 2004;Pizzini, 2006;Cinquini et al, 2007;Russo, 2011;Goldberg andKosinski, 2011, Battaglia andPedretti, 2012;Perazzo et al, 2017;Rejeb et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The hope is that in future organisation will be based on the intensity of the treatment in order to distribute the personnel costs in a homogeneous way on the basis of the levels of comorbidity or gravity (Nicosia & Lagostena, 2008;. However, as previous studies has highlighted (Smaldone and Vainieri, 2016;Nuti et al, 2017;Murante et al, 2017), it is not sufficient to put in place performance measurement systems and tools, these should be disclosed with effective communication strategies throughout the whole organization fostering the cognitive effect of performance measurement and giving feedback information to support the decision-making processes both of physicians and management professionals. Further research could be performed with the aim to consider the adoption of multi-level and multi-dimensional evidence based performance measurement systems, strictly correlated with soft management styles able to promote the sharing of knowledge and leverage learning processes to promote organizational and management innovation.…”
mentioning
confidence: 99%